2017
DOI: 10.22159/ajpcr.2017.v10i4.16757
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Functions in Textile Mill Workers: Role of Peak Expiratory Flow Rate

Abstract: Background: Textile industries play a significant role in the economic growth of the country. Health concern of these textile mill workers is the biggest challenge. Respiratory alterations were found in these workers with long-term exposure to cotton dust. Effect of cotton dust on peak expiratory flow rate (PEFR) is not very well documented in the past.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…Müezzino [13], Spiro and Stigliani [14] and Hendrickson et al [15] have reported the adverse health impacts of textile effluents. Gupta et al [16] have studied 130 male textile mill workers from the different sections of a textile mill their body mass index (BMI) and respiratory functions were evaluated. This study shows with short-term exposure to cotton dust, may also present with respiratory alterations which may increase with long-term exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Müezzino [13], Spiro and Stigliani [14] and Hendrickson et al [15] have reported the adverse health impacts of textile effluents. Gupta et al [16] have studied 130 male textile mill workers from the different sections of a textile mill their body mass index (BMI) and respiratory functions were evaluated. This study shows with short-term exposure to cotton dust, may also present with respiratory alterations which may increase with long-term exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al(20) encontró el PEFR y el IMC > 25 Kg/M2 (p<0.03) pero no para el VEF1 y CVF. En el caso del lugar de residencia resultaba interesante ver si la contaminación ambiental provoca variaciones espirométricas en los operarios hilanderos lo cual no fue significativo en nuestro estudio como si se vio en otros estudios con alteraciones espirométricas en VEF1 -0.1 (-3.2 a 3.1) (5) o del 17.4 % en otro estudio por residir < 1 kilómetro a fabricas(11).…”
unclassified